Relative energy deficiency in sport - Mountjoy, M. (Science + Triathlon 2015 World Conference, 2015)
Recognizing that sport has a positive impact on health and as a leader of the Olympic Movement, whose first objective is to promote Olympism and develop sport worldwide, the IOC has taken a leadership role to improve athlete health. A recent project of the IOC is the IOC Consensus Statement: "Beyond the Female Athlete Triad: Relative Energy Deficiency in Sport (RED-S). This project is based on a meeting of world experts in the field held in Lausanne in November 2013. Topics addressed included a scientific update of the field and the development of clinical tools for athlete diagnosis and return to play. Special emphasis is on expanding the concept of the Triad to better address the underlying cause and to include the male athlete who is also affected by the syndrome.